1995
DOI: 10.1164/ajrccm.151.6.7767521
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of recurrent wheezing in school-age children. The Physicians of Raleigh Pediatric Associates.

Abstract: Correlates of recurrent wheezing were examined in a case-control study involving 343 children ranging from 7 to 12 yr of age and recruited from a general pediatric practice. Positive skin tests for allergy were observed in 35% of a random sample of children without recurrent wheezing, and in 77% and 90% of children who had experienced from two to four episodes and five or more episodes, respectively, of recent wheezing. By logistic regression analysis, sensitization to dust mite (odds ratio [OR]: 5.2; 95% CI: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(23 citation statements)
references
References 30 publications
2
19
0
2
Order By: Relevance
“…The definition of smoking varied across the studies and only few reports used cotinine urine measurements to verify tobacco smoke exposure 5 30 36. Each study included in this review was investigated for possible confounding factors and the data used in meta-analysis were statistically adjusted for these factors when possible (see online supplementary table SI, SII, SIII and table A3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The definition of smoking varied across the studies and only few reports used cotinine urine measurements to verify tobacco smoke exposure 5 30 36. Each study included in this review was investigated for possible confounding factors and the data used in meta-analysis were statistically adjusted for these factors when possible (see online supplementary table SI, SII, SIII and table A3).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies (9033 participants) 4 5 19 22 27 29 33 36 were eligible for dichotomous meta-analysis. In two other reports (4080 children) analysis was based on OR only, we therefore applied generic inverse variance analysis in order to estimate an overall effect.…”
Section: Environmental Tobacco Smoke Ets and Skin-prick Testsmentioning
confidence: 99%
“…Only one study from Nigeria28 reported a substantial reduction in the odds ratio for either parent smoking, from 2.12 to 1.41 after adjustment for pet ownership, indoor mould, cockroaches, wood smoke, and use of mosquito coils. In the remaining five studies the odds ratio for parental smoking was altered little by adjustment: from 1.32 to 1.3 after adjustment for family history of asthma and duration of breast feeding in Sweden33; from 1.44 to 1.49 after adjustment for age, sex, socioeconomic status, gas cooking, indoor mould, feather bedding, and pet ownership in the UK35; from 1.74 to 1.8 after adjustment for family history of asthma and skin prick positivity to common aeroallergens in the USA36; from 1.97 to 1.87 after adjustment for personal and family history of atopic disease, socioeconomic status, indoor mould, and salt preference in South Africa37; and from 2.79 to 2.82 after adjustment for maternal asthma, history of bronchiolitis, and a range of obstetric and perinatal variables in the USA 39…”
Section: Resultsmentioning
confidence: 99%
“…The proportion of children sensitised to A tenuis increased with the number of episodes. However, significant associations were also observed for sensitisation to mites and especially to cats 25. The relation between skin test reactivity and forced expiratory volume in one second was examined in children aged 6 to 12 years with asthma or frequent wheezing as part of the second national health and nutrition survey.…”
Section: Discussionmentioning
confidence: 99%